Space-Base Disaster Management and Poverty Reduction in Nigeria - Okon, Emmanuel Okokondem (American International Journal of Social Science Research, 2018)
Poverty level in Nigeria is at variance with the country’s immense wealth and natural disasters are on the increase and claiming lives as well as properties. This paper looks at the use of space base technology in disaster management and how disaster management can be integrated into poverty reduction to help reduce the vulnerability of poor and protect their livelihoods and development gains. It starts by conceptualizing poverty and vulnerability and proceeds to examine Nigeria’s economy, poverty and natural disaster. Thereafter, the paper looks at the introduction of space technology in disaster mitigation and management in Nigeria and the challenges associated with it. Suggestions are made for effective use of space technology for disaster management and poverty reduction in Nigeria.